Stereotypical Representations of Siberia in Seventeenth Century Translations - Carisio, Anastasiia (Translation Studies: Theory and Practice, 2023)
This paper demonstrates the sociocultural impact of translation by examining reports about Siberia from foreign travelers and writers in the seventeenth century. The main research method is from Jerzy Bartmiński, who founded the Ethnolinguistics School of Lublin, and his cognitive approach (Bartmiński 2009). The current study is a continuation of our extensive research related to the stereotypes that represent colloquial images of Siberia and the Cognitive Definition of Siberia among Spanish speakers on the Iberian Peninsula. This is based on linguistic units found in Spanish corpora spanning from 1736 to 2014. The aim of this paper is to trace how the translation of works by scientists who wrote about Siberia in the seventeenth century contributed to the penetration of stereotypical ideas about this region into different cultures, particularly within Spanish culture.
Keywords: translation; stereotypes; Siberia; cognitive definition